THEORETICAL AND PRACTICAL PROBLEMS OF JUDICIAL REVIEW IN UZBEKISTAN - Xakimov Bunyod Turanazarovich (European Science Publishing, 2024)
This article analyzes the content of the latest reforms in the field of review of court decisions in the Republic of Uzbekistan and its theoretical and practical problems. The analysis is mainly carried out using theoretical and comparative study methods. The main goal of this research is to determine the factors that led to the implementation of the reform in the field of review of court decisions and its initiator, the theoretical and practical problems of the new system.
Keywords: appeal, Supreme Court, instance, civil cases, court decision, cassation, revision, uniformity of judicial practice, court practice, interpretation, application of law.